Relationship between insulin resistance and amino acids in women and men. Issue 5 (7th May 2015) - Seibert, Ryan; Abbasi, Fahim; Hantash, Feras M.; Caulfield, Michael P.; Reaven, Gerald; Kim, Sun H.
Abstract: Insulin resistance has been associated with higher plasma amino acid (AA) concentrations, but majority of studies have used indirect measures of insulin resistance. Our main objective was to define the relationship between plasma AA concentrations and a direct measure of insulin resistance in women and men. This was a cross‐sectional study of 182 nondiabetic individuals (118 women and 64 men) who had measurement of 24 AAs and steady‐state plasma glucose (SSPG) concentration (insulin resistance) using the insulin suppression test. Fourteen out of 24 AA concentrations were significantly ( P < 0.05) higher in men than women; only glycine was lower in men. Majority of these AAs were positively associated with SSPG; only glycine concentration was negatively associated. Glutamic acid, isoleucine, leucine, and tyrosine concentrations had the strongest correlation with SSPG ( r ≥ 0.4, P < 0.001). The degree of association was similar in women and men, independent of obesity, and similar to traditional markers of insulin resistance (e.g., glucose, triglyceride, high‐density lipoprotein cholesterol). Compared with women, men tended to have a more unfavorable AA profile with higher concentration of AAs associated with insulin resistance and less glycine. However, the strength of association between a direct measurement of insulin resistance and AA concentrations were similar between sexes and equivalent to several traditional markers of insulin resistance. Abstract : There has been growing interest in the role of amino acids in insulin‐resistant states with previous studies showing higher levels of certain amino acids in obesity; however, very few studies have used direct measures of insulin resistance to evaluate the relationship between insulin resistance and amino acids. We have directly quantified insulin resistance in 182 women and men using the Insulin Suppression Test and found a sex disparity with men generally having higher levels of amino acids associated with insulin resistance and lower levels of glycine which is inversely associated with insulin resistance. We also found that in both sexes certain amino acids are as strongly associated with insulin resistance as some traditional markers of insulin resistance (e.g., glucose, triglyceride, high‐density lipoprotein cholesterol).